2008
DOI: 10.1002/sia.2877
|View full text |Cite
|
Sign up to set email alerts
|

High‐rate preparation of thin Si films by atmospheric‐pressure plasma enhanced chemical transport

Abstract: Polycrystalline Si films were prepared by chemical transport using near-atmospheric-pressure pure hydrogen plasma (6.7×10 −3 to 5.3 × 10 −2 MPa). Substrate temperatures were varied from 200 to 600• C and solid Si source was used as the feedstock to generate SiH x species. To generate high-density stable glow hydrogen plasma at near atmospheric pressure, 150 MHz very high frequency (VHF) power was used. The dependence of deposition rate on various preparation parameters, such as VHF input power, hydrogen pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…[12][13][14][15][16] In this review article, we describe two new processes to produce purified Si material directly from MG-Si based on the APECT principle. One is the formation of purified Si films using a 150 MHz very high frequency (VHF) H 2 plasma, which is generated in a narrow plasma gap (proximity-type APECT).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16] In this review article, we describe two new processes to produce purified Si material directly from MG-Si based on the APECT principle. One is the formation of purified Si films using a 150 MHz very high frequency (VHF) H 2 plasma, which is generated in a narrow plasma gap (proximity-type APECT).…”
Section: Introductionmentioning
confidence: 99%
“…One is the formation of purified Si films using a 150 MHz very high frequency (VHF) H 2 plasma, which is generated in a narrow plasma gap (proximity-type APECT). [12][13][14][15] The other is a new process of SiH 4 gas formation directly from MG-Si using 2.45 GHz microwave H 2 plasma (remote-type APECT). 16,17) Although the experiments were performed in the H 2 pressure range from 100 to 760 Torr, the acronym ''APECT'' is used throughout this article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous study [12][13][14], we have reported that a poly-Si film with a wedge-shaped columnar structure was formed at a deposition rate of 15 nm/s. The average grain size in the prepared Si film with the thickness of 4.5 μm was about 2 μm.…”
Section: Influence Of He Dilution On Si Film Structurementioning
confidence: 98%
“…For efficient fabrication of Si films, Ohmi et al [11][12][13][14][15] have proposed atmospheric-pressure plasma enhanced chemical transport (APECT) method in which no source gas is needed. In this method, high-pressure (100 -760 Torr) stable glow plasma of pure H 2 is generated between two parallel electrodes (less than 2 mm apart) by supplying a 150 MHz very high frequency (VHF) power.…”
Section: Introductionmentioning
confidence: 99%